2019
DOI: 10.1136/bmjopen-2018-024923
|View full text |Cite
|
Sign up to set email alerts
|

Is the apparently protective effect of maternal nicotine replacement therapy (NRT) used in pregnancy on infant development explained by smoking cessation?: secondary analyses of a randomised controlled trial

Abstract: ObjectiveTo investigate relationships between maternal smoking status in pregnancy and infant development. The largest randomised controlled trial of nicotine replacement therapy (NRT) for smoking cessation in pregnancy, the smoking, nicotine and pregnancy (SNAP) trial, found that at 1 month after randomisation, smoking cessation rates were doubled in the NRT group compared with the placebo group. At delivery, there was no significant difference in cessation rates between groups. Surprisingly, infants born to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 44 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…These papers reported different outcomes. One study investigated infantile colic [ 24 ], two studies infant development impairment and reported respiratory problems [ 25 , 26 ], one major congenital anomalies [ 27 ], and one attention-deficit/hyperactivity disorder [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These papers reported different outcomes. One study investigated infantile colic [ 24 ], two studies infant development impairment and reported respiratory problems [ 25 , 26 ], one major congenital anomalies [ 27 ], and one attention-deficit/hyperactivity disorder [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 2019, another secondary analysis of the SNAP trial was designed to investigate whether the absence of infants’ developmental impairments at 2 years was associated with maternal smoking status measured at different point in the trial [ 26 ]. After adjusting for some potential confounding factors which are known to be associated with infant development, this study did not report a significant association between measures of maternal tobacco smoke exposure and infant development impairment at age 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Studies have shown that nicotine exposure during the fetal (via the placenta) or the postnatal (PN; via breast milk) periods negatively affects the development of the cardiovascular and nervous system of the offspring. [6][7][8] For years, our research group has been investigating a metabolic programming model of maternal nicotine-only exposure during the breastfeeding period and its impacts on the offspring's metabolism. 9 In this experimental model, adult male rats showed increased body mass, increased total adiposity, and adipocyte hypertrophy, both in the visceral and subcutaneous compartments.…”
Section: Introductionmentioning
confidence: 99%